(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article involves teaching German is one of the most challenging aspects of learning the language. It gives full information about the genitive case in German. In English, the dative case is known as the indirect object. Unlike the accusative, which only changes with the masculine gender, the dative changes in all genders and even in the plural. The pronouns also change correspondingly.